Design implementation of an AES-256 hardware accelerator and its side-channel attack (SCA) evaluation - Goh, Xing Han (Nanyang Technological University, 2022)
In this modern era, encryption is one of the commonly used protection measures to ensure data security. It can be used to protect sensitive data from being stolen and being exploited by any adversaries for harmful purposes. Any personal with authorized permission will be able to access or read the data with their personalized key. Therefore, the data will be protected from any attacks as long as the personalized key is being kept well.